Quantum Learning in a Sufism Perspective: Integration of Tajalli Concepts and Holistic Learning Theory - Hamzah, Hamzah; Firdaus, Firdaus; Robiah, Siti; Hamzah, Muhammad Luthfi; Mere, Klemens (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2026)
This study critically addresses the persistent gap in Islamic Religious Education (IRE) between cognitive-oriented instructional practices and the need for transformative learning that meaningfully integrates spiritual experience. Existing applications of Quantum Learning (QL) within religious education largely remain technical and methodological. At the same time, Sufi epistemology, particularly the concept of tajalli, has rarely been theorized as a foundational learning paradigm. This theoretical disjunction limits IRE’s capacity to foster holistic transformation encompassing intellectual, emotional, and spiritual dimensions. Employing a philosophical-analytical approach, this study conducts a hermeneutic analysis of classical Sufi texts, systematically deconstructs the core principles of QL, and synthesizes them with transformative learning theory to formulate an integrative conceptual framework, Quantum Sufic Learning (QSL). The findings argue that learning can be reconceptualized as a process of tajalli, in which meaning is unveiled through the dynamic interaction of rational cognition (‘aql), spiritual-emotional awareness (qalb), and transcendental consciousness (ruh). The study’s primary theoretical contribution lies in advancing a spiritually grounded extension of holistic and transformative learning theory by embedding Sufi epistemology into contemporary educational discourse. Conceptually, QSL offers a transferable pedagogical model that transcends specific cultural or institutional settings, providing a new framework for integrating spirituality and modern learning theory without dichotomizing tradition and innovation. This study contributes to the theoretical development of Islamic education and transformative pedagogy, while inviting future empirical research to examine the effectiveness of QSL across diverse educational contexts.